Antibacterial Drug Shortages From 2001 to 2013: Implications for Clinical Practice. (22nd April 2015) - Quadri, Farha; Mazer-Amirshahi, Maryann; Fox, Erin R.; Hawley, Kristy L.; Pines, Jesse M.; Zocchi, Mark S.; May, Larissa
Abstract : We evaluated national antibacterial shortages over 13 years; 148 drugs were on shortage, with an upward trend. Multiple shortages occurred for 22% of drugs. Shortages of agents used to treat multidrug-resistant infections are of particular concern for clinical management. Abstract: Background.  Previous studies have described drug shortages; however, there has been no comprehensive evaluation focusing on US antibacterial shortages. Methods.  Drug shortage data from the University of Utah Drug Information Service database were analyzed, with a focus on antibacterial agents from 2001 to 2013. We used descriptive statistics to describe trends in drug shortages, analyze drug classes commonly affected, and investigate whether drugs experienced multiple periods of shortages. Results.  One hundred forty-eight antibacterial drugs were on shortage over the 13-year study period, with 26 drugs still active on shortage as of December 2013. The median number of new shortages per year was 10 (interquartile range [IQR], 7). The number of drugs on shortage increased at a rate of 0.35 additional drugs every month (95% confidence interval, .22–.49) from July 2007 to December 2013 ( P < .001). The median shortage duration was 188 days (IQR, 366.5). Twenty-two percent of drugs experienced multiple shortage periods. Conclusions.  There were a substantial number of drug shortages from 2001 to 2013, with a dramatic rise in shortages since 2007. Shortages of agents used to treat multidrug-resistant infections are of concern due to continued transmission and limited treatment options.